2010
DOI: 10.4161/oxim.3.5.13107
|View full text |Cite
|
Sign up to set email alerts
|

Probucol Attenuates Cyclophosphamide‐induced Oxidative Apoptosis, p53 and Bax Signal Expression in Rat Cardiac Tissues

Abstract: Cyclophosphamide (CP) is a widely used drug in cancer chemotherapy and immunosuppression, which could cause toxicity of the normal cells due to its toxic metabolites. Probucol, a cholesterol-lowering drug, acts as potential inhibitor of DNA damage and shows to protect against doxorubicin-induced cardiomyopathy by enhancing the endogenous antioxidant system including glutathione peroxidase, catalase and superoxide dismutase. This study examined the possible protective effects of probucol, a lipid-lowering compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 50 publications
11
56
0
Order By: Relevance
“…Data are presented as mean ± S.E., n = 6 * and # indicate significant change from control, and CP respectively at p ≤ 0.05 using ANOVA followed by Tukey-Kramer as a post ANOVA test. consistent with previous studies (Asiri, 2010;Nagi et al, 2011). CP is a cardiotoxic agent inducing a direct myocardial endothelial damage and destruction of myocardial cells.…”
Section: Discussionsupporting
confidence: 93%
“…Data are presented as mean ± S.E., n = 6 * and # indicate significant change from control, and CP respectively at p ≤ 0.05 using ANOVA followed by Tukey-Kramer as a post ANOVA test. consistent with previous studies (Asiri, 2010;Nagi et al, 2011). CP is a cardiotoxic agent inducing a direct myocardial endothelial damage and destruction of myocardial cells.…”
Section: Discussionsupporting
confidence: 93%
“…This increase showed heart tissue damage, which are related with myocardial infarction, cardiac failure and myocarditis (Figure 2, 3). Similar to our study in many other studies [11,16,26] there was seen an increasing level of CK-MB when treated with CYP. Our biochemical data has been expressed in the same line with other studies which observed a significant increase in AST and CK-MB levels [25,29,32].…”
Section: Tocsupporting
confidence: 92%
“…These may imply that overproduction of reactive oxygen species could be reduced by the HT, in the same line, other studies indicated a decrease in the antioxidantive enzyme activity is a consequence of raised oxidative stress in the heart tissue [34,37]. This results are consistent with numerous researches [11,16,38]. In 150 mg/kg CYP treated group the level of TOC increased, which indicated CYP-related oxidative stress and cardiac toxicity.…”
Section: Tocsupporting
confidence: 87%
See 1 more Smart Citation
“…Oxidative stress together with inflammation induces apoptosis (Alqahtani & Mahmoud, 2016). CP-induced apoptosis is mediated by oxidative stress (Asiri, 2010). Aged black garlic may act as an antimutagenic and protective agent against DNA damage via its antioxidant properties (Abdella & Gad, 2008).…”
Section: Discussionmentioning
confidence: 99%